A socio-history of the media and participation in Uganda - Chibita, Monica; Fourie, Pieter J. (Communicatio, 2007)
This article is based on research done for a doctoral thesis titled Indigenous language programming and citizen participation in Ugandan broadcasting: An exploratory study (Chibita, 2006). The purpose of the thesis was to investigate and show the importance of first-language media for the participation of citizens in democratic processes. The thesis covered a wide range of topics including linguistic perspectives on language and participation, the history, structure and operation of the media in Uganda, the regulatory environment for linguistic diversity in Uganda's broadcast media, debates about indigenous language broadcasting in Uganda, and policy recommendations. In this article, the emphasis is on one of the topics dealt with in the thesis, namely key political, economic and cultural factors in Uganda's history and how these factors, including the right to the use of indigenous languages, have had an important impact on citizens' capacity to participate in public debate through the media (especially broadcasting). It is argued that the opportunities for Ugandans to participate in their governance through critiquing and making an input in government policy have been limited by a number of factors. These include bad colonial and postcolonial policies on the media and language, poverty, low levels of education, and lack of basic access to the means of participation. They have also been limited by governments which have proscribed freedom of expression and association by varying means and to different degrees since the early twentieth century.
Keywords: Diversity; history; media; participation; politics; Uganda